Proceedings of SPE/DOE Enhanced Oil Recovery Symposium 1992
DOI: 10.2523/24195-ms
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Oil and Water Permeabilities Using Gels

Abstract: Several previous researchers reported that polymers or gels can reduce permeability to water more than to oil. However, a plausible explanation for the phenomenon is not yet available. This property is critical to the success of gel treatments in production wells if zones cannot be isolated during gel placement. We examined how different types of gels reduce oil and water ~ermeabilities in Berea sandstone, The eel formulations that we investigated included (1) resorcinkformaldehyde, (2) &+(chloride)-xanthan, (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
27
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 0 publications
1
27
0
Order By: Relevance
“…However, cases have been observed where the effect is significantly more pronounced in cores of intermediate wettability than in water-wet cores. 3 Thus, although we suspect that wettability may play a role in the disproportionate permeability reduction, its effects are unclear.…”
Section: Review Of Previous Findingsmentioning
confidence: 98%
See 2 more Smart Citations
“…However, cases have been observed where the effect is significantly more pronounced in cores of intermediate wettability than in water-wet cores. 3 Thus, although we suspect that wettability may play a role in the disproportionate permeability reduction, its effects are unclear.…”
Section: Review Of Previous Findingsmentioning
confidence: 98%
“…[2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Earlier work (at 41°C) showed that this effect was not caused by simple hysteresis of relative permeabilities or by gel breakdown during successive injection of oil and water banks. 2,3 Thus, the effect does not appear to be an experimental artifact.…”
Section: Review Of Previous Findingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the problem focusses on producer wells, most of the successful treatments documented in the literature were applied on injectors. Reservoir conditions, gel properties and placement protocols influence how effectively gel treatments reduce water coning (1,2) . Although success has been demonstrated both in the laboratory and in the field, no one is in a position to claim a good understanding of why gels work so well in some situations and not in others (2) .…”
Section: Introductionmentioning
confidence: 99%
“…2 Journal of Canadian Petroleum Technology The producing well was completed in layer 14, the bottom oilzone layer. As a result, the completion interval was 1.23 m wide, slightly less than is typical in the field.…”
Section: Introductionmentioning
confidence: 99%